PENGAWASAN OMBUDSMAN TERHADAP PELAYANAN PUBLIK DI KOTA SAMARINDA - Dinny Wirawan Pratiwie S.H.,M.H (Yuriska: Jurnal Ilmiah Hukum, 2015)
The case of public services in the city of Samarinda made an independent institution that is Ombusdsman, in this case, had to intervene itself to supervise the government does not provide good public services, effective, and professional service to the society, so many people who are not satisfied with the public services provided by government and report the matter for authorities to follow up an ineffective of public services in Samarinda.